Cosmic rays measurements with Tunka Radio Extension - Kostunin, Dmitriy (2017)
Tunka Radio Extension (Tunka-Rex) is an array of 63 radio antennas deployed at the Tunka Advanced Instrument for cosmic rays and Gamma Astronomy (TAIGA). This antenna array detects radio pulses produced by deflection of charged component of air-shower in Earth's magnetic field during its development. Tunka-Rex measures cosmic rays of energies above 100 PeV starting from 2012. The hardware description, methods and latest results are given in this ...